STUDI KASUS: ASUHAN KEBIDANAN KOMPREHENSIF PADA NY A UMUR 39 TAHUN DI PUSKESMAS MOJOTENGAH KABUPATEN WONOSOBO - romdiyah, romdiyah; Nenden Intan Febriani; Indrawati Aris Tyarini; Poppy Nurbaeti (Jurnal Ilmiah Kesehatan, 2025)
Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) are the most important indicators to assess the welfare of a country. One of the efforts made by the government is through comprehensive midwifery care using the SOAP method and described in descriptive and narrative form and reviewed continuously (Continuity of Care). The subject taken in this report is Mrs. A, 39 years old at the Mojotengah Health Center, the assessment was carried out from March 13 to May 7, 2025. The results of the study on pregnancy which was examined twice, found that Mrs. A had a high risk, namely pregnancy age ≥35 years and hypertension. During Maternity Care, Mrs. A experienced complications, namely precipitous labor, the baby was born healthy, the neonate was found to have jaundice, postpartum progress, physiological problems, and the mother chose the Implant KB. The conclusion in this assessment was that there was no gap between theory and practice.